Microsatellite variation in potato landraces from the island of La Palma - Ruiz de Galarreta, J. I.; Barandalla, L.; Lorenzo, R.; Gonzalez, J.; Rios, D. J.; Ritter, E. (Spanish Journal of Agricultural Research, 2007)
Nineteen microsatellite markers were used to fingerprint a set of 19 potato landraces from the island of La Palma (Canary Islands). These landraces represent relicts of early introductions from South America, although most are commonly cultivated by local farmers. The SSR primers detected 62 polymorphisms, 13 of which were present in all landraces. Several accession- and group-specific markers were detected. Jaccard similarity coefficients were estimated from the molecular data and UPGMA cluster analysis was performed. Some cultivars with related common names clustered together. In some cases, e.g., for the ‘Conejera’ landrace, the molecular patterns were discrepant with previous species assignments, suggesting the need for a more detailed morphological and comparative study of these accessions